A Hierarchy of DSMLs in Support of Product Life-Cycle Assessment - Nolte, M.; Kaczmarek-Heß, M.; Fritsch, A.; Betz, S. (Association for Information Systems, 2019)
To support understanding and analysis of sustainability related aspects in organizations (e.g., via an assessment of a product’s life-cycle from the cradle to the grave), various instruments, among others, in the field of conceptual modeling, have been proposed. Although existing tools and languages are, to some extent, indeed supporting the product Life-Cycle Assessment (LCA), our investigations show that a hierarchy of Domain-Specific Modeling Languages(DSMLs) is needed to satisfy advanced requirements. In this paper, as an innovation for the field of LCA, we propose an application of multi-level language architecture to design a hierarchy of DSMLs encompassing concepts for LCAs that can be detailed to specific industrial domains and local needs of enterprises. This enables a new generation of instruments allowing users to use and refine concepts, corresponding to their specific needs.